Penerapan Metode Forward Chaining Pada Sistem Pakar Identifikasi Penyakit Tanaman Kelapa Sawit - Dona Marcelina; Evi Yulianti; Zaid Romegar Mair (Jurnal Informatika Global, 2022)
This application of an expert system for identification of oil palm plant diseases aims to make it easier for employees of the Oil Palm Research Center of Sungai Lilin Musi Banyuasin Business Unit to identify oil palm plant diseases based on the symptoms seen then this application provides solutions and appropriate control methods for plant diseases. the oil palm. The data used in this study are data on 10 diseases that exist in oil palm plants and 47 symptoms that appear. The method used in this expert system for identification of oil palm plant diseases uses the Forward Chaining method and the depth-first search tracking technique so that the tracking process will be tested from the first symptom to the last to get a conclusion in the form of the name of the disease along with its causes and how to control it. in this expert system, namely functional testing and expert system testing. Functional testing uses the Black Box method with the Equivalence Patitioning (EP) technique. System testing is carried out by system users, namely. Based on the results of testing with the Black Box method, the developed system functions as expected. Furthermore, expert testing is a test that compares the results of the system diagnosis with the results of expert diagnoses. Expertise test results also show good results. Furthermore, external testing, this test is by giving questionnaires to 35 respondents to get an assessment of the system. The results of the questionnaire (Expert) obtained a satisfaction value of 89.2%Keywords: Oil Palm Disease, Expert System, Forward Chaining Method, depth-first search